Diversitas Ikan Kecil dalam Populasi Teri yang Dijual di Pasar Anduonohu, Kendari - Dewi, Citra Satrya Utama; Ghiffari, Syauqi Muhammad; Yamindago, Ade; Anam, Choirul (Penerbit Brainy Bee, 2025)
Anchovies have an economical price, high nutritional value, and a savory and delicious taste. As a result, they are widely favored by the public and are very easily obtained in traditional markets, including the Anduonohu Market in Kendari. The objectives of this study were to determine (1) the diversity of small fish species in the anchovy population sold at Anduonohu Market, Kendari through morphological characteristics; and (2) the status of these species in IUCN and CITES. The collection of the anchovy population was carried out in December 2021 at Anduonohu Market, Kendari, Southeast Sulawesi. Data analysis of fish species and their status in the International Union for Conservation of Nature (IUCN) and the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) was carried out descriptively by considering the morphology and morphometry of the fish, adjusted to FishBase, a World Wide Web electronic publication www.fishbase.org. There are two types of small fish in Anduonohu Market, namely lureh (anchovy) and small rembang. Meanwhile, in the anchovy population, ten other species of small-sized fish were found. All identified small fish species have an IUCN status of least concern - low risk and have not been evaluated in CITES.